Projected changes to South Atlantic boundary currents and confluence region in the CMIP5 models: the role of wind and deep ocean changes - G M Pontes; A Sen Gupta; A S Taschetto (Environmental Research Letters, 2016)
The South Atlantic (SA) circulation plays an important role in the oceanic teleconnections from the Indian, Pacific and Southern oceans to the North Atlantic, with inter-hemispheric exchanges of heat and salt. Here, we show that the large-scale features of the SA circulation are projected to change significantly under ‘business as usual’ greenhouse gas increases. Based on 19 models from the Coupled Model Intercomparison Project phase 5  there is a projected weakening in the upper ocean interior transport (<1000 m) between 15° and ∼32°S, largely related to a weakening of the wind stress curl over this region. The reduction in ocean interior circulation is largely compensated by a decrease in the net deep southward ocean transport (>1000 m), mainly related to a decrease in the North Atlantic deep water transport. Between 30° and 40°S, there is a consistent projected intensification in the Brazil current strength of about 40% (30%–58% interquartile range) primarily compensated by an intensification of the upper interior circulation across the Indo-Atlantic basin. The Brazil–Malvinas confluence is projected to shift southwards, driven by a weakening of the Malvinas current. Such a change could have important implications for the distribution of marine species in the southwestern SA in the future.